IMPLEMENTASI MODEL PEMBELAJARAN GENRE BASED APPROACH DALAM PENGAJARAN MENULIS TEKS IKLAN (ADVERTISEMENT) MELALUI LESSON STUDY - Istiqlaliah Nurul Hidayati; Mursidah Rahmah (LPPM Universitas Islam 45 Bekasi, 2023)
Writing skill is one of the most important language skills to be mastered by students. There have been many learning models developed for writing especially in English but not all English teachers know and implement these learning models. One learning model that has been extensively researched and proven to be effective in teaching English writing skills is the Genre Based Approach. The English teacher's mastery of the Genre Based Approach learning model is very important because apart from being proven effective, it is also recommended by the government, especially in the implementation of the independent curriculum. It is projected for learning in the coming year, GBA will be required to be used as a model for learning English in schools, including in vocational schools. The service method is carried out using the lesson study model. Lesson study is carried out in three cycles until finally the students get a score that exceeds the KKM score. In addition to quantitative data in the form of increasing students' English writing scores, the volunteers also distributed questionnaires that asked students' perceptions after learning using the Genre Based Approach. From the answers to the questionnaire it can be concluded that GBA cognitively adds to their insights and this insight can be used for ideas in writing and affectively GBA makes them interested and challenged to write.